THE MECHANISM FOR CREATION OF EVENT-DRIVEN APPLICATIONS BASED ON WOLFRAM MATHEMATICA AND APACHE KAFKA - Zolotariov, Denis (Sučasnij stan naukovih doslìdženʹ ta tehnologìj v promislovostì (Online), 2021)
The article is devoted to the research and development of the mechanism of interaction between Wolfram Mathematica programs and Apache Kafka queue to provide the ability to build event-driven applications based on it. The subject of the research is the practical principles of building a mechanism for interaction between Wolfram Mathematica and Apache Kafka. The purpose of the article is to develop and substantiate practical recommendations regarding the formation of a mechanism for publishing messages to the Apache Kafka queue and reading messages from it for programs of the mathematical processor Wolfram Mathematica, which will make it possible to build event-driven applications. Tasks: to determine the mechanism of such interaction, prove the choice of tools for its implementation, create and test the obtained results. The research used the following tools: Apache Kafka, Kafkacat, the method of developing the Wolfram Mathematica package. The results of the research: the mechanism of interaction between Wolfram Mathematica and Apache Kafka was determined and the corresponding toolkit was created on its basis in the form of two Mathematica packages, which are built on using Apache Kafka as a queue client and third-party Kafkacat software, respectively. It is shown that the first option is less reliable and consumes much more computer resources during operation. It has been demonstrated that the Mathematica processor is currently not suitable in its pure form for real-time data analysis. Recommendations are given regarding the use of built-in compilation functions to increase the speed of such processing. Conclusions. Practical recommendations have been developed and substantiated regarding the formation of the mechanism of interaction between the Wolfram Mathematica mathematical processor and the Apache Kafka queue manager for the possibility of working in two directions with the queue: publishing messages and reading them. A toolkit for such interaction in the form of Mathematica packages has been created, their capabilities have been demonstrated, as well as comparison with each other. The economic benefit of using the described tools is shown. Future ways of its improvement are given.